2022
DOI: 10.1002/app.53296
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical performance of fused filament fabrication copolyester by continuous carbon fiber in‐situ reinforcement

Abstract: As one of the most commonly used thermoplastics, polyester has rarely been used as the raw materials of 3D printing. However, copolyester obtained by copolymerization modifying polyester, such as Poly Ethylene Terephthalate Glycol (PETG), has been proven to be suitable for the fused filament fabrication (FFF) technique in previous studies, but the mechanical performance of printed products is still poor. In this paper, 3D printed PETG is in‐situ reinforced by continuous carbon fiber (CCF), and the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Among these reinforcements, CF has been widely used in the manufacture of light weight and high strength composite materials, 19,20 due to its advantages of high modulus, high strength and low thermal expansion coefficient. The mechanism of CF reinforced polymers is that CF can bear the load, and the polymer protects the fiber and transfer the stress to CF 21,22 . It is reported that the tensile strength of PEI was improved from 104 to 168 MPa with the content of 30 vol% CF 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these reinforcements, CF has been widely used in the manufacture of light weight and high strength composite materials, 19,20 due to its advantages of high modulus, high strength and low thermal expansion coefficient. The mechanism of CF reinforced polymers is that CF can bear the load, and the polymer protects the fiber and transfer the stress to CF 21,22 . It is reported that the tensile strength of PEI was improved from 104 to 168 MPa with the content of 30 vol% CF 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of CF reinforced polymers is that CF can bear the load, and the polymer protects the fiber and transfer the stress to CF. 21,22 It is reported that the tensile strength of PEI was improved from 104 to 168 MPa with the content of 30 vol% CF. 23 While there are also some defects in printed CF enhanced materials.…”
mentioning
confidence: 99%
“…Consequently, another XY layer is printed and on completion of the print head or the platform again moves another layer up and the process continues until the whole component is constructed. Myriad of parameters, for example, nozzle temperature, print bed or platform temperature, print layer thickness, printing speed, and infill rate must be optimized to obtain warp‐free thermoplastic product in 3D mode 3 …”
Section: Introductionmentioning
confidence: 99%
“…Myriad of parameters, for example, nozzle temperature, print bed or platform temperature, print layer thickness, printing speed, and infill rate must be optimized to obtain warp-free thermoplastic product in 3D mode. 3 Isotactic polypropylene or PP is among the most popular thermoplastics currently in use for RP using FDM. There are adequate recent references available which show that the PP has been used as an integral component in many blends and composites for fundamental study in 3D processing.…”
mentioning
confidence: 99%
“…2,4,5 Continuous fiber reinforced thermoplastic composites (CFRTPCs) prepared by FDM exhibit excellent mechanical performances, which can improve the customized level to a certain extent and will expand the application of FDM in the field of composites. 6,7 In the previous research, the thermoplastics used to prepare CFRTPCs by FDM are mainly polylactic acid (PLA), 1,8 polyamide (PA), [9][10][11] polypropylene (PP), 12 poly ethylene terephthalate glycol (PETG), 13 poly(ether-ether-ketone) (PEEK). [14][15][16] It is concentrated on thermoplastics with poor heat resistance and mechanical properties, which limit the applications.…”
Section: Introductionmentioning
confidence: 99%